Assessment of Lightweight Aggregate Concrete Using Textile Washing Stone - Room, S. (Institute of Electrical and Electronics Engineers Inc., 2021)
Pumice stone, known as the lightweight aggregate, is a mixture of lava and water used to replace coarse aggregate in construction. Nowadays, lightweight concrete has many applications in the concrete and construction industry. This study aims to overcome the project's cost and re-use the waste material dumped by the textile industry known as a pumice stone. Besides, an attempt has been made to compare the conventional concrete and lightweight aggregate concrete (LWAC) using a mix ratio of 1:1.5:3 and determine the strength parameters of LWAC. Lightweight concrete is made by partial replacement of coarse aggregate with different proportions of pumice stone ranging from 10, 20, 30, 50, 75 and 100. Furthermore, several tests have been conducted to investigate mechanical properties such as compressive strength and tensile strength of lightweight concrete and compare them with conventional concrete. A total of 42 cylinders were cast and prepared, in which 21 cylinders were for compressive strength and 21 for tensile strength. Each set of 3 cylinders was cast for 10, 20, 30, 50, 75, and 100, making 21 cylinders for compressive strength and separate 21 cylinders for tensile strength with the same proportions. The experimental results show that the strength gradually decreases as the percentage of pumice stone increases. Therefore, up to 30 of lightweight aggregate as a partial replacement gives the desired compressive strength. Besides, the split tensile strength decrease when the percentage of pumice stone increases and gives the desired strength up to 30 replacement. Therefore, it is concluded that 30 replaced concrete can be effectively used for structural purposes, whereas 50, 75, and 100 can only be suitable for the non-structural members. Â© 2021 IEEE.